Enantioselective syntheses of β-amino alcohols catalyzed by recyclable chiral Fe(iii) metal complex. Issue 9 (19th January 2016) - Tak, Rajkumar; Kumar, Manish; Kureshy, Rukhsana I.; Choudhary, Manoj Kumar; Khan, Noor-ul H.; Abdi, Sayed H. R.; Bajaj, Hari C.
Abstract : An efficient asymmetric desymmetrization of meso -epoxides with anilines catalyzed by a series of simple and environmentally benign in situ generated Fe(iii ) complexes based on chiral tridentate ligandsL1 –L7 was carried out at rt. Abstract : An efficient asymmetric desymmetrization of meso -epoxides with anilines catalysed by a series of simple and environmentally benign in situ generated Fe(iii ) complexes based on chiral tridentate ligandsL1 –L7 with achiral and chiral linkers (methylene, piperazine, R / S BINOL and diethyl tartrate) was carried out at rt. The in situ generated iron metal complex based on ligandL5 a emerged as improved (low catalyst loading) catalyst for asymmetric desymmetrization of meso -epoxides with anilines giving high enantioselectivity (up to 99%) and high yield (95%) of enantiopure β-amino alcohols in 14 h. While excellent results for ARO of cyclic as well as aliphatic epoxides with anilines was achieved with in situ generated complex from the ligandL4 h and Fe(iii ) chloride, the catalyst was recoverable and recyclable (five times) with retention of its performance.